In-situ X-ray Microscopy of Crack-Propagation to Study Fracture Mechanics of On-Chip Interconnect Structures. (29th April 2018) - Kutukova, Kristina; Liao, Zhongquan; Werner, Stephan; Guttmann, Peter; Standke, Yvonne; Gluch, Jürgen; Schneider, Gerd; Zschech, Ehrenfried
ABSTRACT: Chip-package interaction (CPI) and the related thermomechanical stress in microchips increase the risk of failure in on-chip interconnect stacks, caused by delamination along Cu/dielectrics interfaces (adhesive failure) and fracture in dielectrics (cohesive failure). High-resolution transmission X-ray microscopy (TXM) is a unique technique to image crack propagation in on-chip interconnect stacks. The visualization of crack evolution in Cu/low-k Backend-of-Line (BEoL) structures is demonstrated using an experimental setup which combines high-resolution X-ray imaging with mechanical loading. The application of an indenter manipulator at the TXM beamline of the synchrotron radiation source BESSY II provides an unprecedented level of details on the fracture behavior of microchips. This in-situ experiment allows to identify the weakest layers and interfaces and to evaluate the robustness of the BEoL stack against CPI.